Physical analysis of an electric resistor heating - Perea Martins, J. E.M. [UNESP] (IOP Publishing, 2018)
This work describes a simple experiment to measure the resistor temperature as a function of the applied power and proves that it is an efficient way to introduce some important physical concepts in classroom, including the Joule's first law, hot-spot temperature, thermal resistance, thermal dissipation constant, time constant and the Newton's law of cooling.